KAJIAN KEPEDULIAN MASYARAKAT BERBASIS KEARIFAN LOKAL DALAM UPAYA PELESTARIAN LINGKUNGAN DI DESA PENGLIPURAN BALI - Tina -; M.Taufan Qolby; M. Tsani Alhaq (Program Studi Pendidikan Kependudukan dan Lingkungan Hidup, 2019)
Desa Penglipuran was a village in Bali Province which had local wisdom values and a tourobject which most visited by tourists. Penglipuran village was ruled by a local law which called asawig-awig. The purpose of this research is to describe the urban awareness level based on local wisdomto enviromental conservation in Penglipuran Village. The research method was used qualitative wihdescriptive technique. The population is all Penglipuran village's urban, Bangli. Using randomsampling method, the data where collected by some observation. The data used in this research wasprimary data with questionnaiire given to 30 persons which randomly chosen. The result of thisresearch showed that the local urban had high awareness of conservation based on the present of localwisdom. In this case, Penglipuran village's urban who gas high awareness of environment could beaffected by local insight and local law (awig-awig) which supported the environmental sustainability.